Topical tranexamic acid in elderly patients with femoral neck fractures treated with hemiarthroplasty: efficacy and safety? - a case-control study - Kwak, Dae-Kyung (BMC Musculoskelet Disord, 2019)
BACKGROUND: Perioperative blood management is an important issue in the treatment of elderly patients at an increased risk of postoperative complications. Accordingly, tranexamic acid (TXA) is widely administered to reduce blood loss and transfusion requirements. In this case-control study, the effect of topical TXA on the outcomes of elderly patients with femoral neck fractures after hemiarthroplasty was evaluated. METHODS: This study enrolled elderly patients (age ≥ 70 years) who underwent cementless bipolar hemiarthroplasty for femoral neck fractures between January 2015 and January 2017. The study group comprised 72 patients who received TXA via topical administration during surgery. After propensity matching, the control group comprised 72 patients who did not receive topical TXA. The perioperative and postoperative parameters of the two groups were compared. RESULTS: The estimated blood loss, vacuum tube drainage, and total transfusion volume were significantly lower in the study group than the control (p = 0.024, 0.003, and 0.019, respectively). Despite a lack of significant intergroup differences in the lengths of ICU and hospital stays; rates of ICU admission, venous thromboembolism, delirium, and readmission; and rates of in-hospital and 1-year mortality, the incidence of postoperative medical complications was significantly lower in the study group (p = 0.003). CONCLUSION: Topical TXA administration appears to be a simple and effective option for reducing blood loss, transfusion requirements, and medical complications after hemiarthroplasty in elderly patients with femoral neck fractures.